PENINGKATAN PEMAHAMAN SISWA MENGENAI ASPEK HUKUM PENGGUNAAN PAYLATER PADA E-COMMERCE DI SMA KESATRIAN 2 SEMARANG - Setyowati, Endang; Agus Saiful Abib; Dhian Indah Astanti; Stefani Dewi Rosariad (Jurnal Padamu Negeri, 2025)
The widespread phenomenon of bad debts on PayLater has become a serious problem affecting the younger generation. This community service activity aims to educate the risks of PayLater as a form of early financial literacy prevention at the secondary school level. PayLater requires terms and conditions to be met. However, users often ignore these terms and conditions, resulting in legal consequences. The legal provisions regarding PayLater in e-commerce are regulated by Financial Services Authority Regulation Number 10/POJK.05/2022 concerning Information Technology-Based Joint Funding Services, and the Agreement under Article 1313 of the Civil Code (KUHPerdata). This agreement is considered a standard agreement because it contains terms and conditions made by one party and an electronic agreement made and documented in an electronic document. The community service activity was carried out by the Community Service Team in partnership with SMA Kesatrian 2 Semarang, targeting the school's eleventh-grade students. The community service location is at Jalan Gajah Raya No. 58, Gayamsari, Semarang City. The problem faced by partners is a lack of understanding regarding the legal aspects of using PayLater on e-commerce platforms. Therefore, the Community Service team conducted outreach to provide understanding regarding this matter. This community service activity utilized methods including lectures and question-and-answer sessions to address the partners' concerns. To gauge the students' level of understanding, a pre-test was conducted before the presentation. Following the Q&A session, the community service team provided an evaluation through a post-test.